PENGARUH MODEL COOPERATIVE LEARNING TIPE TEAM GAMES TOURNAMENT BERBANTU ULAR TANGGA PADA PEMBELAJARAN MATEMATIKA KELAS IV SDN 131/II SKB - Amanda Zafirah Ramadhani; Nurlev Avana; Elvima Nofrianni (AL JABAR: Jurnal Pendidikan dan Pembelajaran Matematika, 2025)
The results of initial observations show that students' learning outcomes, especially in mathematics learning, are still relatively low. One of the main causes is the learning approach that is still one-way and does not involve active student participation. Based on these problems, this study aims to determine the influence  of the cooperative learning model  of the Team Games Tournament (TGT) type assisted by snakes and ladders on students' mathematics learning outcomes. The method used was an experiment with a Quasi Experimental Design research design, using the form of Nonequivalent Control Group Design. The subjects of the study were grade IV students in one of the elementary schools, namely class IV B as an experimental class and class IV C as a control class. Data was obtained through multiple-choice tests in the form of pretest and posttest. The results showed that the average posttest of the experimental class was 59.03, higher than the control class which was only 53.22. The Paired Sample Test produced a significance value of 0.042 < 0.05, which shows the influence of the use of the TGT model on learning outcomes. Meanwhile, the results of the Independent Sample T-Test of 0.010 < 0.05 proved that there was a significant difference between the two classes. Thus, it can be concluded that the use of a snake-and-ladder-based TGT type Collaborative models can improve students' math results. This study recommends the application of this learning model, especially in flat building materials in mathematics subjects.